Individual Experiences in Four Cancer Patients Following Psilocybin-Assisted Psychotherapy - Malone, Tara C.; Mennenga, Sarah E.; Guss, Jeffrey; Podrebarac, Samantha K.; Owens, Lindsey T.; Bossis, Anthony P.; Belser, Alexander B.; Agin-Liebes, Gabrielle; Bogenschutz, Michael P.; Ross, Stephen (Frontiers in Pharmacology, 2018)
A growing body of evidence shows that existential and spiritual well-being in cancer patients is associated with better medical outcomes, improved quality of life, and serves as a buffer against depression, hopelessness, and desire for hastened death. Historical and recent research suggests a role for psilocybin-assisted psychotherapy in treating cancer-related anxiety and depression. A double-blind controlled trial was performed, where 29 patients with cancer-related anxiety and depression were randomly assigned to treatment with single-dose psilocybin (0.3 mg/kg) or niacin in conjunction with psychotherapy. Previously published results of this trial demonstrated that, in conjunction with psychotherapy, moderate-dose psilocybin produced rapid, robust, and enduring anxiolytic and anti-depressant effects. Here, we illustrate unique clinical courses described by four participants using quantitative measures of acute and persisting effects of psilocybin, anxiety, depression, quality of life, and spiritual well-being, as well as qualitative interviews, written narratives, and clinician notes. Although the content of each psilocybin-assisted experience was unique to each participant, several thematic similarities and differences across the various sessions stood out. These four participants' personal narratives extended beyond the cancer diagnosis itself, frequently revolving around themes of self-compassion and love, acceptance of death, and memories of past trauma, though the specific details or narrative content differ substantially. The results presented here demonstrate the personalized nature of the subjective experiences elicited through treatment with psilocybin, particularly with respect to the spiritual and/or psychological needs of each patient.